Antimicrobial potential of iodine-containing substances and materials - A. V. Nevezhina; T. V. Fadeeva (Acta Biomedica Scientifica, 2023)
Despite the search and development of new antimicrobial drugs with antibiotic or antiseptic properties, the spread of multidrug-resistant strains of microorganisms remains a serious problem in the treatment and prevention of infectious diseases (wound, postoperative and burn infections, preoperative preparation of the surgical and injection fields, hygienic disinfection of the hands of surgeons, medical personnel, etc.). This review of modern domestic and foreign literature sources is devoted to the analysis of data on the prospects of using antiseptics with iodine and iodides as antimicrobial agents. In modern conditions, there is an increasing number of scientific works devoted to the study and development of various drugs, distinguished by their diversity and their specific application. Antimicrobial iodine-containing compounds can be applied to a wide range of  materials such as textile, plastics, metals, ceramics to make them resistant to microbial and biofilm growth. The article summarized the literature data on the high antimicrobial activity of  iodine both in neutral carriers and in synergy with substances already possessing similar properties. Such complex preparations lose their toxicity to a large extent, having prolonged action with the preservation of their properties. The main mechanisms of antimicrobial action of iodine and iodine compounds are determined by their strong oxidizing ability. Attention is drawn to the spectrum of activity of iodine preparations. Along with the antimicrobial effect, they can promote regeneration processes. In general, innovative iodine preparations with antibacterial and fungicidal properties are promising for medical and other purposes.